Semiconductor memory devices and circuits - Yu, Shimeng (Electrical engineer) (Boca Raton : CRC Press, 2022)
"This book covers semiconductor memory technologies from device bit-cell structures to memory array design with an emphasis on recent industry trends and cutting-edge technologies"--
Semiconductor memory technologies overview -- SRAM -- DRAM -- FLASH memory -- Emerging non-volatile memories.
OCLC-licensed vendor bibliographic record.
Keywords: Semiconductor storage devices; Random access memory